School Readiness Research in Latin America: Findings and Challenges. Issue 152 (June 2016) - Strasser, Katherine; Rolla, Andrea; Romero‐Contreras, Silvia
Abstract: Educational results in Latin America (LA) are well below those of developed countries. One factor that influences how well children do at school is school readiness. In this article, we review studies conducted in LA on the readiness skills of preschool children. We begin by discussing contextual factors that affect what is expected of children upon school entry, and we examine critical aspects of children's developmental contexts in LA. We then review local research on the level and determinants of three readiness skills of preschoolers in LA. Few studies allow comparisons between LA and other regions, but some results suggest that the oral language of children in LA before school entry is lower than in developed countries. These entry‐level differences do not seem large enough to explain the poor educational results obtained by children in LA. We conclude regarding research needed to explain educational results and to inform educational policies.